Understanding aquaculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Aquaculture: biology and ecology of cultured species edited by Gilbert Barnabe 1994 403pp ISBN 0 13 482324 9 (Hbk) ISBN 0 13 482316 8 (Pbk)